2018
DOI: 10.1016/j.scitotenv.2017.11.270
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effects of volcanic ash on biofilm stoichiometry, enzyme activity and community composition in North- Patagonia streams

Abstract: Volcanic eruptions are extreme perturbations that affect ecosystems. These events can also produce persistent effects in the environment for several years after the eruption, with increased concentrations of suspended particles and the introduction of elements in the water column. On 4th June 2011, the Puyehue-Cordón Caulle Volcanic Complex (40.59°S-72.11°W, 2200m.a.s.l.) erupted explosively in southern Chile. The area affected by the volcano was devastated; a thick layer of volcanic ash (up to 30cm) was depos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 133 publications
(193 reference statements)
0
10
0
Order By: Relevance
“…Pumice rafting can generate increased turbidity in streams and lakes (Fig. 2A, B) (Larson, 1993;Inbar et al, 1995;Bisson et al, 2005;Carrillo et al, 2018). As a consequence, light penetration decreases, affecting primary producers (Table 1).…”
Section: Effects Of Tephra In Aquatic Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pumice rafting can generate increased turbidity in streams and lakes (Fig. 2A, B) (Larson, 1993;Inbar et al, 1995;Bisson et al, 2005;Carrillo et al, 2018). As a consequence, light penetration decreases, affecting primary producers (Table 1).…”
Section: Effects Of Tephra In Aquatic Environmentsmentioning
confidence: 99%
“…On the other hand, little is known about the immediate effects of tephra inputs on bacterial communities in stream biofilms. A recent study showed that increased inorganic P levels due to tephra input in streams reduced the activity of alkaline phosphatase, implying a reduction in P-limitation of the biofilm community (Carrillo et al, 2018). It would be of interest to investigate this community further to identify the effects of these changes on community structure (bacterial diversity) and biofilm functioning (enzymatic activity).…”
Section: (A) Bacteriamentioning
confidence: 99%
“…Volcanic activity has been also reported with a high eruption frequency ( Carrillo et al, 2018 ), which has formed numerous hydrothermal fields including Porcelana Hot Spring and Geyser, and Cahuelmo Hot Spring. Cahuelmo Hot Spring is a geothermal site located at the sea level coast of Cahuelmo Fjord, that contains waters rich in metallic minerals and elements such as pyrite, polonium, magnetite, and chalcopyrite ( Mackenzie et al, 2013 ).…”
Section: Biotopes and Ecological Nichesmentioning
confidence: 99%
“…Current understanding of volcanic disturbance effects in streams is mostly associated with ash deposition in pre‐existing channels (e.g. Ayris & Delmelle, 2012; Carrillo et al., 2018). Overall effects range from partial loss of taxonomic and functional diversity (e.g.…”
Section: Introductionmentioning
confidence: 99%